2010
DOI: 10.1111/j.1447-0756.2010.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen administration during superovulation increases oocyte quality and expressions of vascular endothelial growth factor and nitric oxide synthase in the ovary

Abstract: The study showed that estrogen co-injection during superovulation increased the ovarian response, embryo developmental competence and expressions of VEGF and eNOS in the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Estrogen enhances oxidative stress in the kidney [29] and promotes kidney toxicity in the tubules [30, 31]. Estrogen also enhances the serum level of NO as seen in our study [32, 33], and on the other hand, NO is involved in CP-induced nephrotoxicity [34, 35]. Therefore, enhancement of serum level of both estradiol and NO potentially may promote the intensity of nephrotoxicity.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Estrogen enhances oxidative stress in the kidney [29] and promotes kidney toxicity in the tubules [30, 31]. Estrogen also enhances the serum level of NO as seen in our study [32, 33], and on the other hand, NO is involved in CP-induced nephrotoxicity [34, 35]. Therefore, enhancement of serum level of both estradiol and NO potentially may promote the intensity of nephrotoxicity.…”
Section: Discussionsupporting
confidence: 51%
“…We could hypothesize that the protective role of EPO may not only be attenuated by estrogen due to the effect of sex hormone on EPO [40, 41], but also estrogen itself promotes the toxicity intensity via NO production [3235] or other pathways. This study for the first time suggests a need to pay special attention to CP therapy in women who are under estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[383940] Furthermore, NO formation is implicated in the CP-induced nephrotoxicity;[4142] and therefore, in the current study the increased level of nitrite in all the estradiol-treated groups may promote nephrotoxicity. In other word, estrogen promotes NO production, as was observed in Groups 1-3, and NO itself is implicated in CP-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 89%
“…Many studies have shown that enhancing VEGF expression during the follicular phase may be useful in increasing ovarian angiogenesis and the number of predominant follicles destined for ovulation ( Wulff et al, 2002 ; Danforth et al, 2003 ; Shimizu et al, 2003 ; Iijima et al, 2005 ). Our previous studies also demonstrated the importance of an adequate expression of ovarian VEGF in the production of good oocyte quality in aged female by showing that administration of pro-angiogenic factors such as sodium nitroprusside (SNP), leptin, and estrogen during superovulation in aged female mice increased not only in the number and quality of ovulated oocytes, but also in the expression of ovarian VEGF ( Lee et al, 2008 ; Ha et al, 2010 ; Joo et al, 2010 ). These results suggest the possibility that the decreased expression of Id-1 in the ovary with female aging may affect the age-related fertility outcomes via the regulation of VEGF expression.…”
Section: Discussionmentioning
confidence: 87%